Reduced neural suppression at occipital cortex in subthreshold depression - Jinhui Li; Yuheng Tan; Zixin Zheng; Chunliang Feng; Wenjie Fang; Xiaodan Huang; Song Lin; Kwok-Fai So; Lu Huang; Chaoran Ren; Qian Tao (Translational Psychiatry)
Abstract Impaired visual perception and biochemical changes in the occipital cortex have been observed in major depression. However, the neural basis underlying these abnormalities remains yet elusive. Importantly, it remains unknown whether these abnormalities are present in the early stage of depression, known as subthreshold depression (SD). Recognized as a precursor of major depression, SD has gained a growing attention in both research and clinical fields. The current study recruit young adults with SD and demographically matched healthy controls (HC). Experiment 1 utilized a series of psychophysical tasks in a large sample (n = 95), and Experiment 2 used a functional magnetic resonance imaging (fMRI) approach in a medium sample (n = 63). Our results show that the impaired spatial suppression at the behavioural level is accompanied by a significant reduction in neural suppression in the human middle temporal complex (hMT+) and early visual cortex (EVC) within the SD group. Additionally, we found enhanced functional connectivity between hMT+ and the medial prefrontal cortex, anterior cingulate cortex, insula, and postcentral gyrus in the SD group. These findings provide new insights into the psychopathological mechanisms underlying depressive symptoms and highlight the significance of the occipital cortex in the early identification and prevention of depression.